2018
DOI: 10.1002/14651858.cd012069.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate for attention deficit hyperactivity disorder (ADHD) in children and adolescents - assessment of adverse events in non-randomised studies

Abstract: Our findings suggest that methylphenidate may be associated with a number of serious adverse events as well as a large number of non-serious adverse events in children and adolescents, which often lead to withdrawal of methylphenidate. Our certainty in the evidence is very low, and accordingly, it is not possible to accurately estimate the actual risk of adverse events. It might be higher than reported here.Given the possible association between methylphenidate and the adverse events identified, it may be impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
173
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(189 citation statements)
references
References 647 publications
5
173
0
11
Order By: Relevance
“…Low appetite, headaches, stomach ache, and insomnia are the most common side effects of MPH . Accordingly, the majority of the patients in this case series reported an increase in disordered sleep, nervousness, hyperactivity, impulsivity, tics, and headaches after 1 year of MPH use compared with baseline.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Low appetite, headaches, stomach ache, and insomnia are the most common side effects of MPH . Accordingly, the majority of the patients in this case series reported an increase in disordered sleep, nervousness, hyperactivity, impulsivity, tics, and headaches after 1 year of MPH use compared with baseline.…”
Section: Discussionmentioning
confidence: 65%
“…Figure 5depicts hypothesized differences in dopamine levels between individuals with normal weight, individuals affected by overweight/obesity, and individuals treated with MPH.Low appetite, headaches, stomach ache, and insomnia are the most common side effects of MPH 50. Accordingly, the majority of the patients in this case series reported an increase in disordered sleep, nervousness, hyperactivity, impulsivity, tics, and headaches after 1 year of MPH use compared with baseline.…”
mentioning
confidence: 83%
“…These figures are concerning considering how important harm measures are for informing evidence‐based practice . Therefore, we also conducted a systematic review on the adverse events of methylphenidate for ADHD in nonrandomized studies …”
Section: Randomized Clinical Trials On Benefits and Harms Of Methylphmentioning
confidence: 99%
“…Between 2012 and 2018, we conducted two Cochrane systematic reviews on methylphenidate for ADHD . This article explores the main findings in relation to evidence‐based practice and our current understanding of ADHD …”
mentioning
confidence: 99%
“…MPH has been suggested to be useful as a treatment for development stuttering, 5,6 whereas other authors have suggested that stuttering may be an adverse effect of MPH treatment. [7][8][9] In light of these contradictory data, we sought to investigate whether there is evidence of an increased risk of stuttering with MPH treatment in a large pharmacovigilance database, 10 using disproportionality analysis.…”
mentioning
confidence: 99%